2019
DOI: 10.1177/0890117119825525e
|View full text |Cite
|
Sign up to set email alerts
|

Learning Through Story Listening

Abstract: A lthough an essential communication skill, listening does not receive the same attention as speaking. As an often-required class, project or professional event, public speaking takes center stage. A person can experience a range of emotions associated with telling their story including shame, anxiety, and frustration but, depending on how they're being listened to, they may also experience validation, understanding, and empathy. The experience of being listened to and, more to the point, feeling heard can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Because of this, audiences are inspired, discussions are sparked, and learning opportunities are expanded. In this regards, the findings of this study was found to be consistent with other studies conducted previously including(McCann et al, 2019) and (VanSledright & Brophy, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because of this, audiences are inspired, discussions are sparked, and learning opportunities are expanded. In this regards, the findings of this study was found to be consistent with other studies conducted previously including(McCann et al, 2019) and (VanSledright & Brophy, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Teret-teret necessitates a dynamic interplay between the contents, the story’s characters, the storyteller, the audience’s inner psychological factors, and the overall narrative settings. The mechanism is that stories keep young teenagers’ imaginative attention, which motivates them, promotes conversations, and broadens their learning possibilities (VanSledright & Brophy, 1992; McCann et al, 2019). As a result, research shows that positive narrative therapy using traditional fairy tales is an effective strategy for youth psychological well-being (Ruini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that increasing specific self-efficacy may increase the effect of perceived behavioral control on medication adherence. Foundational to the human experience, story listening allows the sharing of information, communicates emotion, and engenders compassion (McCann et al, 2019). Listening to stories may be an effective means of intervening specific self-efficacy for KTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Storytelling can be understood as the performative act of narrating experiences to convey meaning (Archibald, 2008;Christensen et al, 2018;Fuccio et al, 2016), while storylistening is the act of actively and emphatically engaging with a story being told with readiness to be taken somewhere unexpected and commitment to mutual learning (Archibald, 2008;Christensen et al, 2018;Dillon & Craig, 2021;McCann, 2019;Sen, 2023).…”
Section: Storytelling and Storylistening In Fostering Resilience For ...mentioning
confidence: 99%